Report on Preliminary NHA 2005 in Kosovo - Jedomskihh-Eigo, Natalja (World Bank, Washington, DC, 2013)
This is a report which includes preliminary data from the year 2005 and description of potential data sources for National Health Account (NHA) in Kosovo. This year was chosen because it was the only year where data on health expenditures from all existing data sources was available. Natalja Jedomskihh-Eigo (consultant) prepared the report after her visit to Kosovo, 15 - 21 April, 2007. The results outlined in this report were presented and discussed at one-day seminar with stakeholders on 26 June, 2007. The report is intended as a discussion document. It represents the first implementation step of NHA in Kosovo to support formation of the Kosovo NHA technical team to lead the future work on health accounts. This report provides a brief description of existing data, including a review of available sources of information, identification of data gaps and recommendations for improved data collection.